Psychometric Properties of the Emotional Competence Inventory - Short Revised Version (ECI-R) - Bueno,José Maurício Haas (2021)
Abstract A previous study presented the Emotional Competence Inventory, which was designed with basis on the emotional intelligence theory. It was very long and had a disproportionate number of items for each factor. Therefore, this study aimed to seek for validity evidence based on its internal structure and carry out an analysis of items of the short version of the instrument supported by the Item Response Theory (IRT). The study included 626 Brazilian participants with a mean age of 24.8 years (SD = 8.2). They were predominantly females (68.5%) who answered to the 34 items in the instrument. A confirmatory factor analysis showed good fit indices, thus confirming the original structure of the instrument. IRT analyses also resulted in good fit indices and revealed the aspects involved in the increased difficulty of the items in each scale. It was concluded that the instrument shows good psychometric properties and can be recommended for research purposes.